THE RELATIONSHIP BETWEEN THE QUALITY OF SERVICE AND PATIENT SATISFACTION OF BPJS PARTICIPANTS IN THE RAUDHAH 2-7 INPATIENT ROOM OF DR. ZAINOEL ABIDIN BANDA ACEH GENERAL HOSPITAL IN 2023 - Prastama, Myranda; Agustina, Agustina; Hasnur, Hanifah (Psikoislamedia: Jurnal Psikologi, 2025)
This study examines the relationship between the quality of health services and the satisfaction of BPJS patients in the Raudhah 2-7 inpatient ward at Dr. Zainoel Abidin General Hospital in 2023. A descriptive-analytic design with a cross-sectional approach was employed, involving 63 respondents selected through accidental sampling. Data was collected using questionnaires and interviews and analyzed using the Chi-Square test with SPSS version 22. The findings reveal a patient satisfaction rate of 69.8%, with significant associations between patient satisfaction and the dimensions of reliability (p = 0.000), responsiveness (p = 0.000), and empathy (p = 0.000). No significant associations were found with assurance (p = 0.076) and tangible aspects (p = 0.341). It is recommended that healthcare providers enhance service quality to improve patient comfort and satisfaction.